2019
DOI: 10.1101/795930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human astrocytes and microglia show augmented ingestion of synapses in Alzheimer’s disease via MFG-E8

Abstract: Synapse loss correlates strongly with cognitive decline in Alzheimer's disease, but the 20 mechanisms underpinning this phenomenon remain unclear. Recent evidence from mouse models points to microglial cells as mediators of synapse removal, and human genetic evidence implicates microglia in disease risk. Here we demonstrate that microglia from human postmortem brain contain synaptic proteins and that greater amounts are observed in microglia from Alzheimer's compared to non-diseased brain tissue. Further, we o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…We recently proposed that it is more likely that synaptic toxicity imparted by Aβ induces microglia to phagocytose damaged synapses rather than Aβ, limiting the spread of damage [18]. Supporting the suggestion that microglia phagocytose synapses, a recent prepublication shows adult human microglia containing synaptic proteins and that synapses derived from Alzheimer's disease brain are phagocytosed more readily [56]. Alternative roles for microglia in Aβ handling have been proposed, including compacting Aβ via TREM2dependent mechanisms [57,58] or clearing Αβ via non-phagocytic mechanisms [summarised in 52].…”
Section: Microglia and Plaquesmentioning
confidence: 95%
“…We recently proposed that it is more likely that synaptic toxicity imparted by Aβ induces microglia to phagocytose damaged synapses rather than Aβ, limiting the spread of damage [18]. Supporting the suggestion that microglia phagocytose synapses, a recent prepublication shows adult human microglia containing synaptic proteins and that synapses derived from Alzheimer's disease brain are phagocytosed more readily [56]. Alternative roles for microglia in Aβ handling have been proposed, including compacting Aβ via TREM2dependent mechanisms [57,58] or clearing Αβ via non-phagocytic mechanisms [summarised in 52].…”
Section: Microglia and Plaquesmentioning
confidence: 95%
“…Microglia–synaptic interactions in physiological and diseased states are increasingly appreciated. A preprint of one study using confocal microscopy demonstrated increased co‐localization of the endosomal/lysosomal marker CD68, expressed by myeloid cells including microglia, and the presynaptic marker synapsin‐I in post‐mortem human tissue (Tzioras et al., 2019). Here we have used GSDIM to demonstrate increased co‐localization of presynaptic material by microglia in post‐mortem human AD tissue compared to healthy controls and other non‐demented controls with high levels of AD‐type pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This process has two components, an initial detachment of afferent axonal endings from the neuronal somatic membrane and dendrites, followed by the displacement of the detached terminals by microglial cells. It is the latter process followed by astroglial insulation of neurons ) that appears to be responsible for the long-lasting functional deficit observed in patients with Bell's palsy (Graeber et al, 1993) Paolicelli et al, 2011;Parkhurst et al, 2013;Schafer et al, 2012;Svahn et al, 2014;Tremblay et al, 2010;Tzioras et al, 2019;Vasek et al, 2016;Wake et al, 2009;Wang et al, 2020;Weinhard et al, 2018;Zhan et al, 2014). The majority of studies monitoring microglial interactions with synapses have been conducted using confocal and two-photon microscopy.…”
Section: Gsdim Enables Studies Of Pathological Synaptic Turnovermentioning
confidence: 99%
“…Synapse loss is a strong indicator of cognitive decline (60)(61)(62). Synaptic deficits precede amyloid deposition in animal models of dementia (63) and microglial phagocytosis of synaptic material is increased in Alzheimer's patients (52). Ablation of microglia rescues synaptic loss and reduces memory impairment in mouse models of dementia (64).…”
Section: Discussionmentioning
confidence: 99%